Fragments, Cityscapes, Modernity. Kracauer on the Cannebière. (February 2013) - Gilloch, Graeme
Written as a small tribute to David Frisby's inspiring, pioneering work on Critical Theory and the modern cityscape, this essay explores a number of feuilletons and other textual fragments in which the cultural theorist Siegfried Kracauer expresses his enduring fascination with the French port of Marseilles. It is suggested that this city has a two-fold significance for him: firstly, in the vibrancy of its street-life, Marseilles is an exemplary, indeed inspirational, instance of the cinematic qualities of modern urban environments. It is to Marseilles that Kracauer's 1960 Theory of Film is indebted not only for its first formulation but also for its central motif of the quotidian 'flow of life' to which the film camera must attend. Secondly, this seedy city constitutes the preeminent site of 'promiscuous modernity', understood here in two senses: not only as an environment of explicit sexuality and sexual activity/exchange, but also one that is 'for mixing' – that is to say, open and inviting to the most eclectic and outré elements. This notion of promiscuity as the continuous co-presence and curious contiguity of heterogeneous populations and incongruous objects also has its filmic aspect – as Kracauer observes elsewhere, such surreal juxtapositions are also to be found off-set in the costumes and props of the film studio. In its fusion of everyday urban energies and extraordinary eccentricities, the cinematic city of Marseilles takes on a dreamlike quality.